Liames intertextuais: os rastros de Virginia Woolf em The Hours, de Michael Cunningham - Araújo, David Raphael (2019)
Literature is palimpsestic. An anthropophagic parchment that creates innumerable connections and interpretations with other arts and, above all, feeds on itself. Throughout the twentieth century, several authors have marked the history of world literature. In this period of literary, aesthetic and social revolutions, a woman emerged as a milestone in this new way of writing: Virginia Woolf. In 1925, the canonical English author had published her fourth novel, Mrs. Dalloway, one of the pioneering books of a writing technique called the stream of consciousness. With the novel, Woolf coined his name in the history of modern literature and serves, in nowadays, as an archetype for new writers. The novel The Hours (1999), by the American author Michael Cunningham, makes an immersion in the universe of the prestigious writer. The characters of his narrative explain the criticism and the breaking of aesthetic standards and consecrated by Woolf in her books, having as clear inspiration the already mentioned Mrs Dalloway. Cunningham's novel drinks from the source of Woolf and recreates his gaze to the new hours of modernity. Using biographical and bibliographical data of Virginia Woolf, linguistic constructions and the characters of Mrs Dalloway, Cunningham produces and recomposes her history full of symbolism and intricacies with the work of the British, making their ideals reinforced and perpetuated within another time and space. The aim of this work is to observe and demonstrate the traces of Woolf within the Cunningham novel through the theories of Julia Kristeva, among other authors dealing with the intertextual mechanisms of literary studies. In view of the aforementioned points, we hope to demonstrate the intertextuality between the two writings that serve as contemplative and reflective objects about themes that are still so pertinent in our society.